Life cycle energy and greenhouse gas emissions implications of polyamide 12 recycling from selective laser sintering for an injection‐molded automotive component. (7th April 2022) - He, Di; Kim, Hyung Chul; De Kleine, Robert; Soo, Vi Kie; Kiziltas, Alper; Compston, Paul; Doolan, Matthew
Abstract: The selective laser sintering (SLS) process generates waste polymer powders, which can be recycled as feedstock for producing injection‐molded components. Recycling this powder has implications on the life cycle modeling of the SLS product, as well as the subsequent injection‐molded component. This study investigates the life cycle primary energy demand (PED) and global warming potential (GWP) of an automotive fuel‐line clip produced with recycled polyamide 12 (PA12) from an SLS process in comparison to the conventional polyamide 66 (PA66) counterpart, based on real‐world industry data. In addition, the life cycle PED and GWP of an SLS part are examined, with and without recycling PA12 from the SLS process. The results indicate a strong dependence on the approach to evaluate the environmental burden of waste PA12 from the SLS process (cut‐off, mass‐based allocation, economic allocation, and substitution). Compared with the PA66 fuel‐line clip, the recycled PA12 (rPA12) clip reduces the life cycle GWP by up to 26% (cut‐off) or increases by up to 68% (mass‐based allocation). For the SLS part, recycling PA12 powder provides a 42% reduction to its life cycle GWP (mass‐based allocation). Finally, from an expanded two‐part system perspective, the recycling of PA12 from the SLS process provides an 8% reduction in life cycle GWP. Similar trends are shown for the life cycle PED profiles. This study demonstrates the importance of recycling additive manufacturing (AM) wastes within a broader cascading system to improve the environmental performance of AM and the circular economy across industrial systems.